Children with Relapsed or Refractory Nephroblastoma: Favorable Long-term Survival after High-dose Chemotherapy and Autologous Stem Cell Transplantation - Illhardt, T.; Ebinger, M.; Schwarze, C. P.; Feuchtinger, T.; Furtwängler, R.; Schlegel, P. G.; Klingebiel, T.; Greil, J.; Beck, J. F.; Handgretinger, R.; Lang, P. (Klinische Pädiatrie, 2014)
Background: High-dose chemotherapy (HDC) with autologous stem-cell rescue (ASCR) is a treatment option for pediatric patients with relapsed nephroblastoma. We present long term results of 9 patients treated between 1993 and 2013 at our center.Procedure: Reinduction therapy was carried out according to GPOH and SIOP recommendations. The conditioning regimen consisted of carboplatin (1 200 mg/m²), etoposide (800 mg/m² or 40 mg/kg) and melphalan (180 mg/m²). Purging of the grafts with immunomagnetic CD34 positive selection was performed in 5 patients.Results: 8 of 9 Patients (90%) are alive without evidence of disease after a median follow-up of 8.5 years. Leukocyte engraftment occurred after a median of 10 days (range 8–12). Median numbers of 667/µl CD3+, 329/µl CD4+, 369/µl CD8+T cells and 949/µl B cells were reached after 180 days. No negative impact of CD34 selection was observed. No transplantation-related death occurred. Acute toxicity comprised mucositis III°–IV° in all and veno-occlusive disease in one patient. Long term effects probably related to treatment occurred in 3/7 evaluable patients and comprised hearing impairment, reduced renal phosphate reabsorption, mild creatinine elevation and hypothyroidism (n=1, each).Conclusion: Thus, in our experience HDC with ASCR is an effective treatment of recurrent or refractory nephroblastoma with acceptable side effects. However, a randomized trial proving its efficiency with a high level of evidence is needed.
Keywords: nephrobastoma; stem-cell transplantation; high-dose chemotherapy; Wilm’s disease